Recognising floods, recognising people? Flood risk management in riverfront urban kampongs of Indonesia - Mark Wiering; Elizabeth MacAfee; Tara Saharan; Muhammad Damm; Muhammad Irvan; Cindy Rianti Priadi; Maria Kaufmann; Inaya Rakhmani; Edwin deJong (Journal of Flood Risk Management)
Abstract Flood risks can stem from various causes and exhibit distinct characteristics that shape the way they are governed. Depending on flood risk characteristics, specific policies are designed and organisations are involved. In Indonesia, like in other regions, organisational divisions are made for coastal floods, fluvial floods and pluvial floods (resulting from tides, rivers and rain, respectively). The Indonesian cities of Manado and Pontianak both face recurring floods. However, the characteristics of and responses to these floods are different, with consequences for distributive, procedural as well as recognition justice in those cities. In line with Fraser, we define recognition justice in relation to three forms of misrecognition: cultural domination, disrespect, and non‐recognition, with examples from Manado and Pontianak. We show that the misrecognition of certain types of floods overlaps and interacts with the non‐recognition of low‐income informal settlements, disrespect and stereotyping of residents of these areas, and a lack of attentiveness to the culture, livelihoods and practices of people who live alongside rivers. In this way, we examine the landscape of recognition justice in the event of flooding in an urban context, drawing on qualitative interview data gathered from the cities of Manado and Pontianak. The following questions are considered: Who experiences misrecognition? By whom is this misrecognition perpetrated? At which level (institutional frameworks or laws, implementation or social practices) and what are the resulting consequences of this misrecognition? Finally, we explore the interactions between different forms of misrecognition, which create a foundation for further distributional and procedural injustices.